2015
DOI: 10.3390/molecules200915666
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Bran Phenolic Acids: Bioavailability and Stability in Whole Wheat-Based Foods

Abstract: Wheat bran is generally considered a byproduct of the flour milling industry, but it is a great source of fibers, minerals, and antioxidants that are important for human health. Phenolic acids are a specific class of wheat bran components that may act as antioxidants to prevent heart disease and to lower the incidence of colon cancer. Moreover, phenolic acids have anti-inflammatory properties that are potentially significant for the promotion of gastrointestinal health. Evidence on the beneficial effects of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 116 publications
(180 reference statements)
4
109
0
1
Order By: Relevance
“…44,45 Ferulic acid appears to be localized in the aleurone and the hyaline layer, as it has been previously reported. 35,43,46,47 These data suggest the presence of highly feruloylated crosslinked AXs in the wheat bran (wb and Dwb), and show that destarching did not promote the removal of ferulic acid (Fig. 3b).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…44,45 Ferulic acid appears to be localized in the aleurone and the hyaline layer, as it has been previously reported. 35,43,46,47 These data suggest the presence of highly feruloylated crosslinked AXs in the wheat bran (wb and Dwb), and show that destarching did not promote the removal of ferulic acid (Fig. 3b).…”
mentioning
confidence: 67%
“…46,[56][57][58][59] Phenolic compounds are reported to have strong antioxidant activity that can be associated to their ability to destroy oxygenderived free radicals, break radical chain reaction and/or chelate metals. [60][61][62] The DPPH free radical scavenging of FA probably occurs due to its hydrogen-donating ability.…”
Section: Antioxidant Activities Of the Ax Fractionsmentioning
confidence: 99%
“…During storage, the free and bound phenols did not significantly change, confirming retention of their antioxidant potential; moreover, the different wheat bran by‐products had diverse amount of bound phenols, L1, and M1 displaying the highest value. Laddomada et al reported that, along the wheat bran tissues, pericarp, aleurone, intermediate layer, and bran contain the highest amounts of total phenols; on the basis of these data, L1 and M1 probably contained higher amounts of these different wheat bran tissues.…”
Section: Discussionmentioning
confidence: 90%
“…The major process requires a genotypic and phenotypic characterization of key biological processes or pathways that are involved in the assimilation, accumulation, biosynthesis, translocation and remobilization of desired nutritional quality components such as Fe, Zn, vitamins and phenolic acids in the wheat grain [12,15,[37][38][39]. The ultimate process involves the application of biofortiication, which is the most sustainable approach that can reach the nutritional requirements of the global community in a cost-efective manner.…”
Section: Progress In Improving Nutritional Qualitymentioning
confidence: 99%
“…This includes success in increasing the bioavailability of Fe and Zn and decreasing the antinutrients such as phytic acid and polyphenols, which inhibit Fe absorption thereby reducing Fe bioavailability. However, a series of strategies to improve the bioavailability of micronutrients and phenolic acids have been deployed, this includes agronomic biofortiication and the use of nutritional enhancers [27,28,38]. Micronutrients and phenolic acids have also been reported to be pres-ent at high concentrations in the outer layers of the seed and in the wheat germ region than in the endosperm region [18,34].…”
Section: Progress In Improving Nutritional Qualitymentioning
confidence: 99%